Selection of services in UAV Clouds - Rezigat, Aboubakeur Elseddik; Ben Guettache, Hadj Saad; Bousbaa, Fatima Zahra (Université Amar Telidji - Laghouat - Département d'informatique, 2020)
Nowadays, Unmanned Aerial Vehicles (UAVS) cloud have attracted wide attentions from both industrial and academic communities as a new paradigm offering flexible services. This new concept utilizes the recent technologies of mobile cloud computing. The collaboration between these technologies represents a fantastic vision of the future, where everything is con- nected to the Internet, thereby offering intelligent services and facilitating decision-making between cooperative UAVS. In this work, we study the new Unmanned Aerial Vehicle (UAV) clouds computing technol- ogy. Our objectives are to (1) provide a detailed review of the existing services' selection methods and to (2) propose a new Game Theoretic approach for Services' Selection in UAV Clouds (GTSS-UC) aiming to enable normal users to select the most suitable UAV-Service- Provider. Given that every service' provider is characterized by specific features, limitations and prices, a user must select the most suitable provider. The technique of selection is based on the Game Theory (GT) method and takes into account the user requirements and the UAVS provider qualities to find the most adequate provider. The results of the simulation conducted using NS-2 simulator advocate for the eftficiency of our method.